Hybrid Method for Topology Optimization Based on a Meta-Heuristic Method and Pixel Connectivity - Ruzbehi, Shabnam; Hahn, Ingo (IET-PEMD, 2020)
One of the recent developments in engineering optimization is the topology optimization. This method is common in mechanical engineering and optimization of mechanical structures, but it can be used to design novel structures of the electromagnetic devices and electrical machines. In general, topology optimization results need a further development or post-processing to gain a device, which is more adapted to the manufacturing process. Therefore, a hybrid optimization method is offered, which is based on a meta-heuristic method like the Genetic Algorithm (GA). Because of irregular shapes of the optimized topologies, a local method, called pixel connectivity technique, is presented to regularize the structure in a two-level optimization with a focus on the improvement of the meta-heuristic method via GA and post-processing inspired by an image processing method. The Finite Element Method is used to analyse a well-known E-core actuator developed by applying the proposed topology optimization method as a case study. The optimization goal is to achieve the greatest savings of material and gain a lighter weight of the device, while preserving the electromagnetic force at an appropriate level. It is possible to extend and apply this proposed method to different active components of electrical machines in combination with other goals.<br
Keywords: TOPOLGY OPTIMIZATION; PIXEL CONNECTIVITY; REGULARIZATION METHOD; BINARY METHOD; HYBRID METHOD.

Hybrid Structure Optimization of a PMSM Using Global and Local Methods for Higher Torque and Lower Volume - Ruzbehi, Shabnam; Hahn, Ingo (11th IEEE International Conference on Renewable Energy Research and Applications, ICRERA 2022, 2022)
In this work, a Structure Optimization procedure of a permanent magnet synchronous motor is shown, based on a hybrid method to gain a lower weight structure, lower torque ripple and cogging torque, and to preserve the torque as high as possible. As structure optimization is faced with a highly complex structure, to overcome this drawback a hybrid optimization method using a global and a local method is suggested. This hybrid method not only gains a smoother structure but also gains better technical results with considerable reduction of calculation time compared to non-hybrid simple optimization. The proposed hybrid method validity is approved on the rotor and permanent magnet (PM) part of a permanent magnet synchronous motor. The results lead to material and cost reduction, from another side to an improvement of the flux linkages and back-EMF waveforms. Also, torque ripple and cogging torque reduction lead to lower vibration and acoustic noise.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Genetic algorithms; PMSM; Sensitivity method; Topology optimization; Torque; Torque ripple

Magnetic Direction Analysis of Permanent Magnet in a Permanent Magnet Synchronous Machine - Zollet, Bastian; Ruzbehi, Shabnam; Hahn, Ingo (2022 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2022, 2022)
In the optimization of permanent magnet synchronous machines (PMSM), the properties of the magnets play a significant role. The magnetization direction of the permanent magnets is determined during their manufacturing process. By varying the magnetization direction, it is possible to influence the torque and cogging torque delivered by the machine. In the present work, different magnetization patterns are analyzed regarding their effects on these characteristics. The magnetization directions considered are parallel, radial, and parabolic magnetization as well as two different versions of Halbach magnetization. Applying these magnetization directions, torque, torque ripple and cogging torque are determined using simulation in FEMM 4.2 based on the finite element method. During the production of the machines, tolerances inevitably occur that additionally influence these parameters. Selected tolerances are also investigated using the finite element method.
CRIS-Team Scopus Importer:2022-09-02
Keywords: cogging torque; finite element method; magnetization direction; manufacturing tolerances; PMSM; ripple; torque

Post-processing Topology Optimization of an Electromagnetic Actuator Using a Hybrid Method of Genetic Algorithm and Local Importance Measure (LIM) - Ruzbehi, Shabnam; Hahn, Ingo (2019 9th International Conference on Power and Energy Systems, ICPES 2019, 2019)
In the modern design and to improve the operation characteristics of electrical machines and electromagnetic devices an optimal structure of the machine's active and flux guiding parts is required. In the conventional optimization geometric or parameter optimization is common. In these methods, just the boundaries of the shape can be changed. In this study topology optimization as a powerful tool is used. It gives more freedom to the designer to gain higher performance and to approach more close to the consumer goals.In this work, a combinatorial optimization method based on a meta-heuristic algorithm combined with a local method based on a Local Importance Measure is offered to improve the results. The aim of this research is to seek for material distribution inside the electromagnetic actuator to have a lighter weight and the maximum possible force or torque. It is possible to extend this method to the different active parts of electrical actuators and machines satisfying different goals.
Created from Fastlane, Scopus look-up
Keywords: genetic algorithms; global optimization; hybrid algorithm; local optimization; metaheuristic algorithm; topology optimization

Structural Optimization of an Electromagnetic Actuator Based on Genetic Algorithm, Greedy Search and Their Combination - Ruzbehi, Shabnam; Hahn, Ingo (IEEE International Symposium on Industrial Electronics, 2019)
In the last years, optimal operation and usage of electrical machines leads to an increased attention for improving the operating behaviour and changes in the electrical machine's structure for industrial applications. In conventional optimization, it is common to use parametric design and geometric optimization, but this manuscript presents the structural or topological optimization. This method gives more freedom to the designers to adapt high performance electrical machines to the customer goals. The implementation of the proposed method for structural design and topology optimization is applied to the detailed design of an electromagnetic actuator.In general, electrical machinery is aimed to produce high torque and power at minimum weight to gain a high torque and power density. Therefore, high force or torque and low weight are the two main goals in this work for designing electrical machines, which can satisfy mechanical, structural and magnetic constraints. To show the validity and the opportunities of the proposed optimization method, the design of a simple magnetic actuator using a metaheuristic global optimization method (genetic algorithm (GA)) and a deterministic local search (greedy algorithm) is investigated at first and, secondly, a combination of both of these methods is presented for a highly nonlinear problem. The given design goals have been successfully achieved using the proposed structural optimization method to find the best suited topology.
CRIS-Team Scopus Importer:2019-08-23
Keywords: genetic algorithms; global optimization; greedy algorithm; local optimization; metaheuristic algorithm; topology optimization

Structural Optimization of PM Synchronous Machine Based on Multi-objective Algorithm for Lower Torque Ripple and Volume - Ruzbehi, Shabnam; Hahn, Ingo (2022 23rd International Conference on the Computation of Electromagnetic Fields, COMPUMAG 2022, 2022)
In this study, a Topology Optimization procedure of a 36kW permanent magnet synchronous motor (PMSM) is presented to minimize the weight, torque ripple and cogging torque, also to ensure the maximum average torque in a reasonable amount using a novel Evolutionary Algorithm. The structure of the rotor and magnets, which are effective in the performance and weight of PMSM are optimized together and compared with the conventional design. In order to show the validity of methodology performance, also to investigate electromagnetic and operational performances of the motor, the magnetic field is analyzed using finite element method with FEMM software in a discretized design area and online optimization process via Matlab. The results lead to better flux linkage and back-EMF wave shape, and torque ripple and cogging torque reduction, which cause acoustic noise and vibration improvement. This new Topology Optimization method can be extended to other active parts of the machine with different objective functions.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Genetic algorithm; Permanent magnet synchronous machine; Topology optimization; Torque

Topology optimization of a nonlinear electromagnetic actuator based on a local importance measure - Ruzbehi, Shabnam; Hahn, Ingo (Proceedings - 2019 IEEE Workshop on Electrical Machines Design, Control and Diagnosis, WEMDCD 2019, 2019)
Optimal usage of electrical machines lead recently to an increased attention to have machines with improved operating behaviour and changes in the mechanical structure of these machines. In this study, a topological optimization technique based on local gradients is applied to a magnetic actuator, replacing the conventional methods, which are called geometric or parametric optimization. This new method gives more freedom to the designers, in order to gain high performance electrical machines according to the customer's goals. The design space is discontinuous and consists of simple square cells. In this new method, the more important cells with respect to some optimization criteria will determine the optimal topology. The goal is to seek for material distributions that reduce the weight while preserving the magnetic force or torque at a specific level. To show the validity of this method, at first, this method will be applied to a problem with two types of materials (air and iron). Afterwards it will be extended to three types of materials (air, iron and copper), which extremely improves the objective function's value. The gained results verify the validity of the improved method. The results in this case study indicate that this method operates well. Furthermore, it is shown that the proposed method can be extended to gain new shapes of the different active parts of a motor or a transformer to finally reach optimal designs of electromagnetic devices.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Design optimization; Global optimization; Sensitivity; Topology optimization

Topology optimization of a PMSM based on a local method to gain lightweight structure and better operation - Ruzbehi, Shabnam; Hahn, Ingo (11th International Conference on Power Electronics, Machines and Drives (PEMD 2022), 2022)
In this study, a Topology Optimization procedure has been applied to a 3-phase permanent magnet synchronous machine (PMSM) to gain a lighter weight motor with lower torque ripple and cogging torque, while the average torque maintains at a reasonable level with a novel local method, named Local Importance Measure (LIM). The validity of this method is checked with an electrical machine's permanent magnet and rotor part to reduce production costs, permanent magnet and material consumption, and reach a better motor performance. To give more freedom to the designers, replacing the conventional parameter optimization, topology optimization is used. To overcome continuous grey optimization with intermediate material characteristics, a discretized binary method is applied. The electromagnetic field is calculated by using the 2D finite element software FEMM, and the optimization is processed via Matlab. The results verified the method's validity in reaching to a machine design with lower torque ripple and cogging torque, which causes less vibration and acoustic noise. In addition, an improvement in the flux linkage and back-EMF waveform is gained. It is shown that the proposed method can be extended to different kinds of electromagnetic devices, with different objective functions.
Keywords: TOPOLOGY OPTIMIZATION; PMSM; BACK-EMF; TORQUE; COGGING TORQUE.

Topology Optimization of a PM Synchronous Machine Based on Novel Metaheuristic Algorithm for Lower Cogging Torque and Magnet Volume - Ruzbehi, Shabnam; Hahn, Ingo (Proceedings of the IEEE International Conference on Industrial Technology, 2022)
This paper proposes the Topology Optimization procedure of a three-phase permanent magnet synchronous motor (PMSM) to minimize weight, torque ripple and cogging torque, while preserving the average torque using a Binary Evolutionary Algorithm. To show the validity of the proposed topology optimization method, the design of the electrical machine's permanent magnet part is performed to enhance the merits of PMSM, with reduced production costs, lower permanent magnet consumption and improved motor performance. The magnetic field is calculated using the 2D finite element software FEMM in a discretized design area. The optimization process is done via MATLAB. The results show an improvement in the flux linkage and back-EMF waveform. Also, torque ripple and cogging torque reduction lead to less vibration and acoustic noise. The proposed topology optimization method can be extended to other active parts of the machine with different objective functions.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Back-EMF; Cogging torque; Genetic algorithms; PMSM; Topology optimization; Torque

Topology Optimization with Improved Genetic Algorithm of an Electromagnetic Actuator - Ruzbehi, Shabnam; Hahn, Ingo (2019 22ND INTERNATIONAL CONFERENCE ON THE COMPUTATION OF ELECTROMAGNETIC FIELDS (COMPUMAG 2019), 2019)
CRIS-Team WoS Importer:2020-09-04

Two-level Topology Optimization based on a Metaheuristic Method and Morphological Reconstruction - Ruzbehi, Shabnam; Hahn, Ingo (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
This paper offers a Topology Optimization (TO) method to replace conventional parameter optimization, which is a common method for electrical machine’s or electromagnetic device’s design optimization. In most of the final designs gained with TO, there are challenges in the manufacturing process using the nowadays available manufacturing technologies. Therefore, this work investigated the approach on two tasks, in the first level a global optimization method, called Enhanced Binary Genetic Algorithm is applied to the design domain. After optimization with this meta-heuristic method, some holes inside the structure or some spread iron cells appear. This drawback will be improved in the second level by one of the image processing methods, called Morphological Reconstruction, to gain a smoother shape to reduce the manufacturing complexities while reaching reasonable technical characteristics. The goal is to find a lighter weight of the structure while preserving the force in a suited amount. The proposed method is applied to an E-core actuator as a case study. After using the proposed hybrid optimization method, air cells appear around some parts of the actuator’s coil, which are used to extend the copper areas, so that the magnetic force considerably increases. In general, it is possible to extend the method to different active parts of the electrical machines.<br
Keywords: Morphological Reconstruction; Binary Genetic; Algorithm; topology optimization; Actuators

Two-level topology optimization of an electromagnetic actuator based on genetic algorithm and neighbourhood method - Ruzbehi, Shabnam; Hahn, Ingo (Proceedings of the IEEE International Conference on Industrial Technology, 2020)
In this paper a multi-objective topology optimization method is presented to find an innovative design and to improve the conventional iron core structures, which are used in rotary electrical machines and electromagnetic devices. The goals are to find an optimal material distribution with less material usage, which makes the device lighter, and also considering the magnetic force to remain in a reasonable range. At first, a meta-heuristic method, called Enhanced Binary Genetic Algorithm (EBGA) is used to gain an optimal material distribution. In the next step, as a post-processing task, a Neighborhood method is used to improve the technical results, to remove the voids inside the iron shape and to make the structure more suitable for the manufacturing process according to the nowadays available manufacturing technologies. This method is inspired by the image processing technique. Afterwards, a third type of material (copper) is added to the design domain. Air cells, which surround some parts of the copper coil area, will be replaced by copper. With these three steps the amount of force increases significantly, while a lighter optimal shape is obtained. As a case study, the proposed method is tested on a simple electromagnetic nonlinear actuator. The results of this work show that it is possible to extend the method to different active parts of electrical machines such as permanent magnet, stator and rotor.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Genetic algorithm; Magnetic actuator; Multi-level optimization; Neighborhood method; Topology optimization